Emulating the paired-pulse facilitation of a biological synapse with a NiOx-based memristor - Hu, S. G. (2014)
We study the paired-pulse-induced response of a NiOx-based memristor. The behavior of the memristor is surprisingly similar to the paired-pulse facilitation of a biological synapse. When the memristor is stimulated with a pair of electrical pulses, the current of the memristor induced by the second pulse is larger than that by the first pulse. In addition, the magnitude of the facilitation decreases with the pulse interval, while it increases with the pulse magnitude or pulse width.